Viable Options for Diversification of Rice in Non-conventional Rice–conventional Wheat Cropping System in Indo-Gangetic Plains - Shahane, Amit Anil; Shivay, Yashbir Singh (International Journal of Bio-resource and Stress Management, 2019)
The Indo-Gangetic plain (IGPs) is a relatively homogenous ecological region in terms of vegetation. This plains follows mainly‘Non-traditional rice-traditional wheat’ cropping system in Trans and upper IGPs and ‘Traditional rice-non-traditional wheat’ cropping system in middle and lower IGPs. The rice and wheat serve and still serving as a backbone of Indian food security with 76 % share in total food-grain production. The growing concern of adverse impact of rice cultivation in ‘Non-traditional rice-traditional wheat’ were reflected in to depletion of water resources, degradation of soil fertility and environmental problems such as pollution due residue burning and ground water pollution. This creates a scope for diversification of this system to bring sustainability of resource use in Indo-Gangetic plain. The potential options available for diversification of rice in this system include replacement of rice with maize or suitable legumes or oilseeds or cash crops (sugarcane or cotton) or horticultural crops. Along with these options, introduction of medicinal and aromatic plants and break crops also stand as potential options. Diversification through changing cultivation methods and resource management strategies in rice production system is also possible. The present review discusses the reasons for diversification of rice in ‘non-traditional rice-traditional wheat’ cropping system along with needs and issues of rice diversification in IGPs. In this review, attempt has been made to suggest different viable options available for diversification of rice in this cropping system with the help of research done on this issue in IGPs.